Representações identitárias de professores de língua inglesa em textos autobiográficos - Castagnara, Maria Helena (2019)
This research is inserted in thefield of Applied Linguistics, in the area of teacher education, and has as its main theme teachers’ identity. The general aim is to investigate six English Language (EL) teachers’ identity representations, in oral classroom discussion and written autobiographical texts, in the light of theories of Human and Social Sciences, by means of enunciative marks. As specific objectives, we have: a) to investigate participant teachers’ experienced conflicts/challenges, represented in their autobiographical texts; and b) to investigate participant teachers’ achievements/conquers and future expectations, represented in their autobiographical texts. This research context refers to an extension workshop taught by the researcher to six EL teachers, who –at the time of the workshop –were students at a language stricto sensupostgraduate program. The workshop lasted eight hours and was offered in March 2019, with the main objective of provoking some reflections on the teachers’ teaching practice. During the participation in the workshop, the EL teachers attended to a talk about identity and teacher education, read theoretical texts (GAMERO; CRISTÓVÃO, 2013; SILVA, 2011), discussed subjects related to the profession and wrote an autobiographical text. The transcriptions of the audio recorded classes of the workshop and the written texts constitute the data generated to this research. Data analysis was carried out based on Sociodiscursive Interactionism (BRONCKART, 2006, 2008, 2012), especially by the identification of the enunciative mechanisms, which have as categories, the person’s index, voices and modalizations. As a support to the research data analysis interptetation we used references from Social Sciences (HALL, 2003, 2014, 2016; WOODWARD, 2014), Linguistics and AppliedLinguistics (SAUSSURE, 2006; BAKHTIN, 2016; LEFFA, 2013; D'ALMAS, 2016, AUDI, 2019, to name a few), Philosophy (FOUCAULT, 2012), and even from Literature (ALBERTI, 1991). The results show that the participant teachers’ identity representations were shown not only to come from their pedagogical practice, but also from their experience as students, from the family's incentive to study and learn a second language and from the assessment they themselves make on what it is like to be a teacher in our country. We realize that the conflicts and challenges of the profession are diverse, and related to the dealing with students in the classroom, the need for better professional qualification, the challenges in the realization of the teaching practicum, the routine as a student in a postgraduate course and the need for better physical structure and financial investments in schools. With regard to the participants’ achievements and realizations, we identified the enrollment and permanence in the master's program, because both one and the other require the participants a lot of effort and determination. Concerning future expectations, these refer to the permanence in the classroom, end of the master's degree program, continuity in the academic field and pursue a career as a university professor. This way, we understand that investigating teachers’ identity implies entering into a subjective universe, that concerns the life experiences of each one of the research participants. Therefore, even trying to delimit in the analyses elements that may be common in the identity of EL teachers, we cannot ignore the fact that each subject is unique, and even though some experiences present in the participants’ written and oral texts "seem" to be the same, they took place in different contexts and moments, which makes them diverse. Finally, in relation to the participation in the workshop conducted by the researcher, we perceive that this promoted some identity resignification to the EL teachers who took part of the research.